Zdorov'e sportsmena: Kriterii ocenki i prognozirovanija - Apanasenko, G. l.; Cistjakova, Ju. S. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The requirements to the health of an athlete, based on the principles of normology, can be realized only at a stage of selection and initial sports training. In the process of increasing the skill level of an athlete he has more and more deviations from "norm", testifying about the reorganization of the systems of an organism with involving the mechanisms of compensation for the achievement of a result.